PERKEMBANGAN ASURANSI JIWA SYARIAH DI INDONESIA - Susi Kusmawaningsih (IQTISHADUNA, 2022)
Sharia insurance is an insurance business field that has received considerable attention among the people of Indonesia today. As an alternative business, sharia insurance is relatively new to develop in Indonesia. This is enough to attract the attention of the insurance business world in line with the rapid development of the sharia banking business. Sharia insurance is an insurance business field that has received great attention among the people of Indonesia. As an alternative insurance business, Islamic insurance is relatively new compared to the conventional insurance business. The novelty of the sharia insurance business is the operation of its business activities based on sharia principles sourced from the Koran and hadith as well as the Fatwas of the Ulama, especially those collected in the Indonesian Ulema Council (MUI). The principle that distinguishes sharia insurance from conventional insurance is that sharia insurance eliminates elements of uncertainty (gharar), elements of speculation or gambling (maisir), and elements of interest (riba) in their business activities so that insurance participants (insured) feel free from tyrannical practices that harm them. The reason for establishing sharia insurance is because the majority of Indonesians are Muslim, consider the implementation of conventional insurance that already exists is not in accordance with sharia principles because it contains elements of obscurity (gharar), contains elements of gambling (maisir), and contains elements of interest money (riba). The material legal sources of sharia insurance are Islamic sharia, while the sources of Islamic sharia are the Koran, Hadith, Ijma (Ijtihad), Fatwa of the Companions of the Apostles, Qiyas, Istihsan, and Urf (tradition), the Koran and Hadith are the main sources of Islamic law, but in setting the principles -principles and practices and operations of sharia insurance, the parameter that is always a reference is Islamic sharia. The concept of sharia insurance is based on the Qur'an Surah Almaaidah verse (2) which means: "Please help you in doing good and piety, and do not help in committing sins and transgressions". Asuransi syariah merupakan bidang uasaha asuransi yang memperoleh perhatian cukup besar dikalangan masyarakat Indonesia kini. Sebagai usaha alternatif, asuransi syariah boleh dikatakan relatif baru berkembang di Indonesia. Hal ini cukup menarik perhatian dunia usaha asuransi seiring dengan perkembangan pesat bisnis perbankan syariah. Asuransi syariah merupakan bidang bisnis asuransi yang cukup memperoleh perhatian besar dikalangan masyarakat Indonesia. Sebagai bisnis asuransi alternatif, asuransi syariah boleh dikatakan relatif baru dibandingkan dengan bidang bisnis asuransi konvensional. Kebaruan bisnis asuransi syariah adalah pengoperasian kegiatan usahanya berdasarkan prinsip-prinsip syariah yang bersumber dari alquran dan hadis serta Fatwa Para Ulama terutama yang terhimpun dalam Majelis Ulama Indonesia (MUI). Prinsipnya yang membedakan asuransi syariah dengan asuransi konvensional adalah asuransi syariah menghapuskan unsur ketidakpastian (gharar), unsur spekulasi alias perjudian (maisir), dan unsur bunga (riba) dalam kegiatan bisnisnya sehingga peserta asuransi (tertanggung) merasa terbebas dari praktik kezaliman yang merugikannya. Alasan pendirian asuransi syariah adalah karena penduduk Indonesia mayoritas beragama islam, menganggap pelaksanaan asuransi konvensional yang sudah ada kini tidak sesuai dengan prinsip syariah karena mengandung unsur ketidakjelasan (gharar), mengandung unsur perjudian (maisir), dan mengandung unsur bunga uang (riba). Sumber hukum material asuransi syariah adalah syariah Islam, sedangkan sumber syariah Islam adalah Alquran, Hadis, Ijma (Ijtihad), Fatwa Sahabat Rasul, Qiyas, Istihsan, dan Urf (tradisi), Alquran dan Hadis merupakan sumber utama hukum Islam, namun dalam menetapkan prinsip-prinsip maupun praktik dan operasional asuransi syariah, parameter yang senantiasa menjadi rujukan adalah syariah Islam. Konsep asuransi syariah didasarkan pada Alquran Surat Almaaidah ayat (2) yang artinya: “Tolong-menolonglah kamu dalam mengerjakan kebajikan dan takwa, dan jangan tolong-menolong dalam berbuat dosa dan pelanggaran”.